2019
DOI: 10.3329/bjms.v18i2.40710
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the bacterial pathogens associated with hospital acquired infections in hospitals within makurdi metropolis, middle belt, nigeria.

Abstract: Background: Nosocomial bacteria are bacteria that cause diseases acquired from the hospital environments. Aim: This study looked into profile of bacterial pathogens associated with nosocomial infections in hospitals within Makurdi metropolis. Result: A total of 71 bacterial pathogens were encountered from 240 samples analysed from three hospitals in Makurdi metropolis. Of the 71 isolates, 46(64.8%) were Gram positive and 25(35.2%) were Gram negative. The Gram positive constituting S. aureus (50.70%) and staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
6
7
0
Order By: Relevance
“…These patients were reviewed and analyzed. The rest of the patients were categorized as colonizer 19 , age below 13 year old 6 , missing information and missing data 8 as well as those who had positive culture CRAs < 48 hours of ICU admission 5 . The total of ICU admission during the study period was 1,256 patients and the prevalence of CRAs over 24 months was 7.3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients were reviewed and analyzed. The rest of the patients were categorized as colonizer 19 , age below 13 year old 6 , missing information and missing data 8 as well as those who had positive culture CRAs < 48 hours of ICU admission 5 . The total of ICU admission during the study period was 1,256 patients and the prevalence of CRAs over 24 months was 7.3%.…”
Section: Resultsmentioning
confidence: 99%
“…A review on the use of tigercycline for MDR Acinetobacter infections showed that tigecycline had considerable, though not consistent, antimicrobial activity against MDR (including carbapenem-resistant) Acinetobacter spp. However, data to support its clinical use, particularly for ventilator-associated pneumonia or bacteraemia, caused by these pathogens are still limited [17][18][19][20] . There were few limitations in our study.…”
Section: Resultsmentioning
confidence: 99%
“…It represents up to 40 % of all infections acquired in the hospital 17 , where the risk factors for nosocomial UI were the female gender; the urinary catheterization and the historical antecedent of repeated UTIs. However, the study conducted in Nigeria by Onifade et al 18 looked into profile of bacterial pathogens associated with nosocomial infections in hospitals within Makurdi metropolis where 71 bacterial pathogens were encountered from 240 analyzed samples showed that nosocomial pathogenic bacteria, in particular Staphylococcus aureus, Pseudomonas aeruginosa, Staphylococcus spp and enteric bacteria, Escherichia coli and Klebsiella spp are the predominant pathogens associated with infection acquired in hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical microbiologists and infectious disease specialists are agreed that MDR Gram-negative bacteria cause the ultimate risk to public health. The trend of resistance development is more in Gram-negative organisms; also the detection and development of new antibiotics to fight against these bugs are extreme rarer 16,17 .…”
Section: Discussionmentioning
confidence: 99%